AN EVALUATION OF CHILDREN'S PERFORMANCE ON CERTAIN COGNITIVE, AFFECTIVE, AND MOTIVATIONAL ASPECTS OF THE SYSTEMS AND SUBSYSTEMS UNIT OF THE SCIENCE CURRICULUM IMPROVEMENT STUDY ELEMENTARY SCIENCE PROGRAM. - Allen, Leslie R. (Journal of Research in Science Teaching, 1973)
The article presents a study which aims to investigate the elementary students' participation in the Science Curriculum Improvement Study elementary science program. There was an evaluation of the students' performance on certain aspects of the systems and subsystems unit of the science curriculum improvement study elementary science program. Using the input variables of science program membership, sex, socio-economic status, and California Test of Mental Maturity scores and the criterion measures which are described, these children are statistically superior in both cognitive and motivational behavior.